RECYCLABLE HOUSEHOLD WASTE MANAGEMENT THROUGH WASTE BANK IN BATAM ISLAND - Hilda Putri Fatima, Helmya
Batam City, which is located on Batam Island, is one of the industrial cities in Indonesia. Limited land for Final Processing Sites (TPA) prompts the need for better municipal waste management to reduce the burden of landfills. On the other hand, population growth in Batam City continues to increase until it reaches a figure of 2.32% during 2010 – 2020. The enhancement of population certainly greatly affects the increase in the tonnage of household waste generated. The waste bank is present as a government effort to overcome the management of recyclable household waste based on community participation. Waste banks are not only developed as an educational strategy to the community on the importance of waste sorting and reuse of waste that still has use-value or economic value but waste banks can also be used as a means of improving the economic status of the community because the waste trade will generate a turnover/profit. However, the role of waste banks in overcoming waste management on Batam Island is still not optimal, so this study discusses the potential of waste banks in the waste management process and its relation to (economic) trade value, namely the concept of recycling waste management which emphasizes the use-value of goods. Methods of collecting data in this study are direct survey (observation) and sampling. Two types of sampling techniques used are purposive sampling and snowball sampling. Both of these data collection techniques used a structured interview method to obtain information by certain objectives. The data processing is carried out using descriptive analysis techniques to show the management conditions that have been carried out in the study area, namely in nine sub-districts on Batam Island. Based on the results of the study, waste banks can reduce the burden of TPA by 1.97% of household waste, which is 308.97 tons of segregated recyclable waste per year and a total of 287.39 tons of recyclable waste per year sold to the recycling industry. The types of recyclable waste are sorted through the waste bank, the most of which is from the type of paper waste as much as 210.59 tons/year or 68.16% of the total recyclable waste sorted through the waste bank. The turnover of paper waste trade is also the highest type of waste trade turnover which reached Rp 242,330,569.00. It is also known that based on the results of the analysis, the waste bank that contributes the most to waste bank activities on Batam Island is from Batu Aji District. The total amount of paper waste, plastic waste, and metal waste sorted through the waste bank from this sub-district is 165.49 tons/year; 67.78 tons/year; and 14.37 tons/year. With 54 waste banks with the most customers on Batam Island as many as 1570 people, it can be seen that the waste banks in Batu Aji District are the most active compared to waste banks in the other eight sub-districts. Based on the overall results of the research analysis, the waste banks on Batam Island can be classified into three types based on their recycling capacity and turnover. The most dominant waste bank class is Class 1, with 207 units based on their recycling capacity and 200 units based on their turnover. This means that 207 waste bank units have a recycling capacity of fewer than 2 tons/year and there are 200 waste bank units with a turnover of less than IDR 2,800,000. This value is of course still very small when compared to the amount of household waste and similar household waste generated by the domestic activities of the residents of Batam City. Therefore, further development of waste banks is still very much needed to achieve optimal results. The results of this recyclable waste management study can be used as a basis for consideration in making better, profitable, and environmentally friendly waste management policies on Batam Island.